Analysis of the Effect of Palm Oil Productivity on Indonesian Palm Oil (CPO) Supply Chain Management 2015-2021 Through Government Policy as a Mediation Variable - Lumbanraja, Pretty Luci; Lumbanraja, Penny Chariti (Talenta Publisher, 2024)
Supply chain management is important for palm oil companies so it is necessary to analyze the capacity and quality of trading actors, analysis related to control and distribution. So that production output supply chain mapping can be carried out to ensure production, distribution and marketing systems are effective and efficient. This research aims to determine the influence of palm oil productivity measurement variables on palm oil supply chain management through government policy as an intervening variable. This research is exploratory in nature using inferential analysis techniques. Information used in the time setting framework for the 2015-2021 period. This research uses simple linear regression statistical data analysis with the Structural Equation Model (SEM) with the alternative Partial Least Square (PLS) method. The research results show that the influence of palm oil productivity is significantly positive on government policy (0.000) < (0.05) with an estimated magnitude of 0.552. And the influence of government policy is significantly positive on supply chain management (0.000) < (0.005) with an estimated magnitude of 0.834. In this case, there is a positive and significant influence of palm oil productivity on supply chain management through government policy.